Evaluasi Pengadaan Obat Berdasarkan Pelayanan Distributor Farmasi Di RSIA Kemang Medical Care Jakarta Selatan Periode Juli Desember 2019 - Nur Hasanah; Nurwulan Adi Ismaya; Lela Kania Rahsa Puji; Bayu Prihantoro (STIKes Kharisma Persada, 2021)
Drug management is one of the pharmaceutical management in the Hospital which is very important in the overall service. Stages of drug management in the Hospital include the stages of selection, planning, procurement, receiving, storage, distribution, and use of drugs. Patnership with Pharmacy Wholesalers needs special attention because it can influence the procurement of pharmaceutical preparations in hospitals. This study aimed to the determine the process of prucurement of drugs based on distributor services (Pharmaceutical Wholesalers) at RSIA Kemang Medical Care. Retrospective data collection methods. The sample includes data on Drug Purchase Requests for the period July 1 - December 31 2019 for weekly defects made by the Pharmacy Installation of RSIA Kemang Medical Care every Monday, totaling 302 samples. Service Level based on the type / order item for 13 Pharmaceutical Wholesalers (PBF) 88,55% - 98,43% Supplier Service Level based on the precentage of the number of pharmaceutical preparations there are Pharmaceutical Wholesalers (PBF) that have never been in accordance with the requested shipment, ranging from 2% - 100%. The factors that cause incomepatibilty are empty stoc at distributors and there is a shortage in shipping pahrmaceutical preparations.